2022
DOI: 10.1371/journal.pone.0269590
|View full text |Cite
|
Sign up to set email alerts
|

Gardnerella vaginalis clades in pregnancy: New insights into the interactions with the vaginal microbiome

Abstract: Gardnerella vaginalis (GV) is an anaerobic bacterial species involved in the pathogenesis of bacterial vaginosis (BV), a condition of vaginal dysbiosis associated with adverse pregnancy outcomes. GV strains are categorized into four clades, characterized by a different ability to produce virulence factors, such as sialidase. We investigated the distribution of GV clades and sialidase genes in the vaginal ecosystem of a cohort of pregnant women, assessing the correlations between GV clades and the whole vaginal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Th e commensal microbiota of the vagina, which is mostly represented by lactobacilli, is crucial for protection against the translocation of microbiota from other biotopes, as well as conditionally pathogenic and pathogenic microorganisms that can be transmitted sexually. Th e change in the qualitative and quantitative composition of the vaginal microbiota is clinically manifested by such nosological forms of the disease as bacterial vaginosis, vaginal candidiasis, as well as vaginitis with a predominance of aerobic microorganisms that can manifest pathogenic properties [4,7]. Th e results of some studies revealed a clear link between the use of antibiotic therapy along with probiotics containing mainly lactobacilli and the restoration of the vaginal microbiota leading to a decrease in the risk of urogenital infection relapse.…”
Section: Results Th E Formation Of Bacterial Vaginitis In the Balb/c ...mentioning
confidence: 99%
“…Th e commensal microbiota of the vagina, which is mostly represented by lactobacilli, is crucial for protection against the translocation of microbiota from other biotopes, as well as conditionally pathogenic and pathogenic microorganisms that can be transmitted sexually. Th e change in the qualitative and quantitative composition of the vaginal microbiota is clinically manifested by such nosological forms of the disease as bacterial vaginosis, vaginal candidiasis, as well as vaginitis with a predominance of aerobic microorganisms that can manifest pathogenic properties [4,7]. Th e results of some studies revealed a clear link between the use of antibiotic therapy along with probiotics containing mainly lactobacilli and the restoration of the vaginal microbiota leading to a decrease in the risk of urogenital infection relapse.…”
Section: Results Th E Formation Of Bacterial Vaginitis In the Balb/c ...mentioning
confidence: 99%
“…31,71 We also found that the number of Gardnerella clades present was associated with PTB (in non-rarefied samples), and presence of multiple clades has been associated with BV. 21,70 Fewer studies have included PTB as the outcome variable than BV, and results have also been mixed. A study that included a larger sampling of the Stanford and UAB Enriched cohorts found that a V4 variant of the 16S rRNA gene which maps to clades 1 and 2 was associated with PTB in its Stanford cohort, but not its UAB cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Clades 1 through 4 have been associated with BV in at least one of these studies, and clades 5 and 6 were typically not measured. 21,30,32,70 Some studies have evaluated the associations of these genomic species with BV, and have also found varying results. 31,71 We also found that the number of Gardnerella clades present was associated with PTB (in non-rarefied samples), and presence of multiple clades has been associated with BV.…”
Section: Discussionmentioning
confidence: 99%
“…One potential way by which postpartum infections can be alienated is thorough screening of women for bacterial infection at late trimester. As an illustration, a recent study across a cohort of 61 Caucasian pregnant women at the first and third trimester of pregnancy investigated the distribution of Gardnerella vaginalis clades in the vaginal ecosystem and found a correlation between Gardnerella vaginalis clades and the whole vaginal microbiome ( 61 ). Gardnerella vaginalis is notable for been responsible for a significant number of infections in postpartum women worldwide and a leading cause of preterm birth and neonatal infection.…”
Section: Methodsmentioning
confidence: 99%